Análisis de la evolución temporal de las desigualdades con datos irregulares - Francisco Javier Callealta Barroso; Eugenio M. Fedriani Martel; Ana M. Martín Caraballo; Ana María Sánchez Sánchez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2012)
– This article provides a tool to study over time the distributions of income in a population, regardless the irregular distribution of data. We even approach Lorenz curves at the times when we lack the required data. Finally we apply the present technique to a European country where inequalities are particularly relevant: Spain.
Keywords: D31; D63; C81; 330; Lorenz curve; Gini index; irregular time series; income distribution